In vitro bioactivity and phytochemical evaluation of extracts from aerial parts of Eremostachys macrophylla Montbr. & Auch. growing in Iran - P. Asgharian; A. Delazar; A.M. Vatankhah; M. Javadzadeh; S. Asnaashari (Iranian Society of Pharmacognosy, 2017)
Background and objectives: The aerial part extracts of Eremostachys macrophylla  from Labiatae family, which has been traditionally used in wound healing, snake bites, rheumatism and joint pains, were investigated for general toxicity, anti-proliferative, free radical scavenging and anti-bacterial effects.Moreover, preliminary phytochemical investigations were carried out on the extracts. Methods: Extracts were prepared using a soxhlet apparatus with n-hexane, dichloromethane (DCM) and methanol (MeOH), respectively. Brine shrimp lethality test (BSLT) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay were performed to evaluate general toxicity and free radical scavenging properties, respectively. Anti-proliferative and anti-bacterial activities were assessed by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay and disc diffusion methods, respectively.  MTT assay was carried out on one normal and two cancer cell lines including human umbilical vein endothelial cells (HUVEC), human colorectal adenocarcinoma (HT-29) and human lung carcinoma (A-549), respectively. Additionally, all the extracts were tested for the presence of various phytoconstituents by different reagents. Results: The n-hexane extract was the most active fraction in BSLT whereas the MeOH extract showed significant free-radical-scavenging activity. The results indicated that the n-hexane and MeOH extracts possessed anti-proliferative effects against HT-29 cells while all the three extracts were effective against A-549 cell line. None of these three extracts showed any significant effect against HUVEC.The extracts didn't show any antimicrobial effects against Gram positive, Gram negative and Candida albicans species. Conclusion: Considering the results, the species might be a good candidate for further phytochemical and biological studies for the isolation of active and pure ingredients and clarification of anti-neoplastic mechanism.